Acid Effect Sulphate Against Strong Concrete Press Containing Lime As Substitutions of Cement and Glass As Substitution of Coarse Aggregate - Bima Arifian T. R; Syafwandi,; Donald Essen; Acep Hidayat (Journal of World Conference (JWC), 2021)
Lime as a concrete mixture is done because lime contains elements of calcium oxide (CaO) which is the material for the manufacture of cement from 60-65% (Tjokrodimuljo, 2007). Glass waste comes from the waste glass industry has a silica content of 72.20% (Fikriansyah and Tanzil, 2013). The use of these two materials as a concrete mixture of substitution material is expected to reduce the pollution of the CO2 gas environment due to the burning of steam from the manufacture of cement and natural resources exploitation due to excessive aggregate mining. This research aims to determine the influence of sulphuric acid from 2% for strong concrete emphasis that contains glass in lieu of coarse aggregate and lime as a cement substitution. Penelitian ini menggunakan campuran lime dari 7% dan 10% dari berat semen, serta 5% dari limbah glass, dan 9% dari berat kerikil. Compressive strength testing is carried out on the 7th, 14th, 21th, and 28th days. Results of this study showed that the strong emphasis of concrete with a lime mixture of 10% + 5% Glass on 28 days obtained a strong press of 12.13 MPA higher than normal concrete ie 7.68 MPA on the 28th day.